Pengaruh Financial Ratio Dan Ukuran Perusahaan Terhadap Return Saham Perusahaan Batu Bara Yang Terdaftar Di Bei - Caroline dan Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to find out determine the effect of financial ratio and company size on stock return of 11 coal companies which are listed on the Indonesia Stock Exchange (BEI) for period 2008-2016. The research was designed as a descriptive study and verification by using secondary data. Data were analyzed using panel data multiple linear regression and t-test with 99 observations. Multiple linear regression model using fixed model based on Chow Test and Hausman Test.The results showed that profitability give positive significant to stock return, while company value, company size, liquidity, solvability and activity ratio do not have significant to stock return.